Pedagogical and Scientific Heritage of Professor of Riga Polytechnic Institute Mikhail Berlov (1867–1935) - Svetlana Kovaļčuka; Alīda Zigmunde (History of Engineering Sciences and Institutions of Higher Education)
The pedagogical and scientific activity of a mechanical engineer, a faculty member (1897–1918) of Riga Polytechnic Institute (RPI), Professor (1904) Mikhail Berlov (Михаил Берлов; 1867–1935) at the end of the 19th century and in the first half of the 20th century was related to Riga, as well as the Russian city of Ivanovo-Voznesensk (at present – Ivanovo). M. Berlov was the first Rector of the Ivanovo-Voznesensk Polytechnic Institute (IVPI; 1918–1921), who returned to Riga in 1921, obtained Latvian citizenship, and worked at the Russian Technical School of Nikolai Okolo-Kulak. The research also revealed the contribution of the pedagogue and scientist to the compilation of textbooks that were used in the Russian Empire, including in the territory of present-day Latvia in the first half of the 20th century and in the first years of the Republic of Latvia.